Sustainability, lean and eco-efficiency symbioses - Alves, Anabela Carvalho (2016)
A literature review was conducted aiming at investigating the use of Sustainability, Lean, Green and eco-efficiency concepts, as well as meaningful combinations of those, on the field of Production and Operations Management. The study reports on the scientific papers published in all major journals in the field over the period 2001-2015. A set of 83 papers from 40 journals were selected for further analyzes, aiming at uncovering the existing level of awareness and use of the synergic and symbiotic relationship between Lean Manufacturing and Green Production. The findings show that a modest share of papers, about 30 %, explicitly recognize the Lean-Green joint approach. The same study testifies a clear growth pattern, which is patently reinforced in the last two and a half years, on the number of papers that behold a combined approach towards more efficient and cleaner production activities. The research has highlighted that the Lean-Green link does, in fact, exist and is gaining momentum, but requires further reinforcements from the scientific community, as well as from the companies, to deliver excelled and environmentally sound production systems.